2020
DOI: 10.1016/j.jempfin.2020.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Investigating tail-risk dependence in the cryptocurrency markets: A LASSO quantile regression approach

Abstract: We construct the complete network of tail risk spillovers among major cryptocurrencies using the Least Absolute Shrinkage and Selection Operator (LASSO) quantile regression. We capture important features of the network, including major risk-driving and major risk-receiving currencies, and the evolution of the tail dependence among the currencies over time. Importantly, we reveal a striking finding that the right tail dependence among the cryptocurrencies is significantly stronger than the left tail counterpart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“… Corbet, Katsiampa and Lau, 2020a , Corbet, Katsiampa and Lau, 2020b suggest that Bitcoin is a strong safe haven for oil and a weak safe haven for the stock market. Hedging strategies involving Bitcoin could also lower the portfolio's risk and improve the portfolio performance ( Guesmi, Saadi, Abid, et al, 2019 ; Kajtazi & Moro, 2019 ; Nguyen, Chevapatrakul, & Yao, 2020 ). Differently, Bouri, Jalkh, Molnár, et al (2017) find that Bitcoin is a poor hedging instrument, suited only for diversification.…”
Section: Literature Reviewmentioning
confidence: 99%
“… Corbet, Katsiampa and Lau, 2020a , Corbet, Katsiampa and Lau, 2020b suggest that Bitcoin is a strong safe haven for oil and a weak safe haven for the stock market. Hedging strategies involving Bitcoin could also lower the portfolio's risk and improve the portfolio performance ( Guesmi, Saadi, Abid, et al, 2019 ; Kajtazi & Moro, 2019 ; Nguyen, Chevapatrakul, & Yao, 2020 ). Differently, Bouri, Jalkh, Molnár, et al (2017) find that Bitcoin is a poor hedging instrument, suited only for diversification.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In other words, in the same spirit as Borri (2019) and Nguyen et al (2020), who focused on cryptocurrencies and tail-relationships, we present herein a generalization of the approach by Hautsch et al (2014), with estimations of financial networks focusing on dynamic ES. Indeed, Hautsch et al (2014), when estimating the impact of other companies on the VaR of targeted companies, made use of a penalized quantile regression, thus not fully dealing with potential dynamic evolutions in the conditional quantiles.…”
Section: Introductionmentioning
confidence: 99%
“…Hautsch et al [6] constructed a risk spillover network by the interdependence between firms' tail risk exposures of more than 100 financial firms of the United States, and found that risk contagion among financial firms was the main cause of market systemic risks. Nguyen et al [8] map the entire network of tail risk dependence among 21 major cryptocurrencies and find that Bitcoin and Litecoin are the major drivers of tail risk when markets are bullish, and Ethereum and Ethereum Classic are major drivers of tail risk when markets are bearish. Li et al [9] use the sample of 19 international financial markets to analyze the tail risk contagion between international financial market during the COVID-19 epidemic.…”
Section: Introductionmentioning
confidence: 99%